Coadministration of 13-valent pneumococcal conjugate and quadrivalent inactivated influenza vaccines in adults previously immunized with polysaccharide pneumococcal vaccine 23: a randomized clinical trial. Issue 2 (1st February 2019) - Thompson, Allison R.; Klein, Nicola P.; Downey, H. Jackson; Patterson, Scott; Sundaraiyer, Vani; Watson, Wendy; Clarke, Keri; Jansen, Kathrin U.; Sebastian, Shite; Gruber, William C.; Scott, Daniel A.; Schmöele-Thoma, Beate
ABSTRACT: Immune responses to 13-valent pneumococcal conjugate vaccine (PCV13) and quadrivalent inactivated influenza vaccine (QIV) in older adults may vary with coadministration and previous pneumococcal polysaccharide vaccination. This study assessed safety and noninferiority of immune responses to coadministered PCV13 and QIV compared with each vaccine given alone. Adults ≥50 years old preimmunized with ≥1 dose of 23-valent pneumococcal polysaccharide vaccine (PPSV23) ≥1 year before enrollment were randomized 1:1 to receive PCV13+QIV then placebo 1 month later or placebo+QIV then PCV13 1 month later. Administration of PCV13 and placebo was blinded; QIV was administered open-label. Pneumococcal serotype-specific opsonophagocytic activity (OPA) geometric mean titers (GMTs) 1 month after PCV13, and influenza hemagglutination inhibition assay GMTs 1 month after QIV were measured. Prespecified noninferiority was demonstrated by a lower bound of the 2-sided 95% CI for geometric mean ratios >0.5. Safety endpoints included proportions of subjects with adverse and serious adverse events. Of 882 randomized subjects, 846 comprised the evaluable immunogenicity population. Immune responses to all 13 pneumococcal serotypes and all 4 influenza strains 1 month after PCV13+QIV were noninferior to responses 1 month after each vaccine given alone. No safety concerns were identified. Immune responses to coadministered PCV13 and QIV were noninferior to responses after each vaccine given alone, although generally lower for coadministered PCV13. PCV13 and QIV can be administered concomitantly to adults ≥50 years of age preimmunized with PPSV23.